Overview of the emissivity measurements performed in WEST: insitu and post-mortem observations. (1st September 2022) - Gaspar, J.; Corre, Y.; Rigollet, F.; Aumeunier, M.-H.; Bernard, E.; Brezinsek, S.; Courtois, X.; Dejarnac, R.; Diez, M.; Dubus, L.; Ehret, N.; Fedorczak, N.; et al.
Abstract: This paper summarizes the emissivity measurements performed on the plasma-facing units (PFU) of the WEST lower divertor during the first phase of WEST running with a mix of actively cooled ITER-like PFUs made of bulk tungsten (W) and inertially cooled PFUs made of graphite with a coating of tungsten. In situ assessments of the emissivity and laboratory measurements after removing the W-coated graphite and ITER-grade PFUs from the WEST device are shown. The measurements exhibit a complex pattern with strong emissivity variation as a function of space and time mainly explained with the variation of magnetic equilibrium (strike point location) as well as the plasma performances during the experimental campaigns. The exposed ITER-grade PFU exhibits sharp spatial variation of the emissivity from 0.05 to 0.85 at a monoblock scale (12 mm) at the transition of the erosion (strike point location) and deposition (next to the strike point location) areas on the high-field side. On the low-field side, the emissivity varies from 0.12 at the strike point location, to 0.2 a few cm away in the low-field-side direction. This emissivity range after exposure is much higher than the emissivity variation of unexposed PFU with emissivity from 0.09 to 0.15. In situ observation performed on the W-coated graphite PFU shows a rapid evolution, typically a few pulses, of the emissivity in the inner and outer strike point location. The whole spatial distribution is discussed as well as its variation due to the plasma operation from the start-up of WEST to the removal of the W-coated graphite components.